Effect of Cadmium on Antioxidase System in Process of Maize Germination - Xue, Hongbao; Zhang, Hui; Chang, Hualan; Jiao, Yanna; Li, Hui (Asian Journal of Chemistry, 2015)
In order to know something about toxicity mechanism of heavy metals on plants and to improve tolerance of plants to heavy metal poison, the changes of oxidative metabolism and the molecular mechanism in plants under heavy metal stress were explored in the paper. In this test, the maize seeding that has certain tolerant ability to cadmium was used as material. After the maize seeding was treated by different Cd2+ concentrations varied from 5 to 100 μmol L-1 for 12 h, reactive oxygen metabolism of the seeding was comprehensively investigated and antioxidant enzyme activities with different dose of cadmium treating the seeding was analyzed based on the latest structural information about antioxidant enzyme reported. From the latest structural information about enzymes in the Protein Data Bank (PDB), it is indicated that during germination of cadmium-tolerant maize, antioxidant enzyme system (SOD, POD, CAT, APX) has been found to act effectively as oxygen free radical scavenger in a certain range of Cd2+ concentration, while Cd2+ concentration goes slightly beyond the threshold most antioxidant enzymes are easy to loss activities, because malondialdehyde is the production of lipid peroxide inside cells, its higher content reflects that plasma membrane is severely damaged. Moreover, content of active oxygen such as hydrogen peroxide, superoxide anion, etc. produced in metabolic processes has a higher level, which is highly toxic to the organism especially the plasma membrane. Therefore, it can be concluded that there are significant differences in the different activities of antioxidant enzymes under different conditions. Those experimental results have also verified the information about the molecular structures of 4 antioxidant enzymes given above.